LUCY and LILA - Fletcher, Alison; Lyles, Christopher (New York : Little Bee Books, 2016)
"One day in art class, the teacher asks Lucy and her classmates to draw pictures of what they did last weekend. Lucy draws her adventures with a pink elephant named Lila! Her classmates think she's making the whole thing up. But is she?"--
Keywords: English fiction -- Readers; Elephants -- Juvenile fiction; Art -- Juvenile fiction